(untitled) (Anuário Antropológico, 2023)
This article reconstructs the professional journey of its author and, taking morality and values in politics as its guiding thread, seeks to trace various theoretical and methodological developments relevant to the contemporary anthropological debate. From this perspective, it presents the investigations undertaken during her career and their connections to publications, courses, and supervisions at undergraduate and postgraduate levels, research groups and laboratories, as well as national and international networks with which these were (and are) articulated. As the title suggests, it sets out from studies of the feminist movement, followed by investigations in diverse institutional contexts with the inclusion of government policy forums set up under the principle of participatory citizenship.